Naturalized Alien Plant as Traditional Medicine Resources: A Study from Cibodas Biosphere Reserve, West Java - Aisyah Handayani; Ervizal Amir Muhammad Zuhud; Decky Indrawan Junaedi (Department of Forestry, Faculty of Agriculture, University of Lampung, 2023)
Cibodas Biosphere Reserve, with Gunung Gede Pangrango National Park as the core zone area, has an enormous number of naturalized alien species spread within it. There are 88 alien plant species, and more than 50% are utilized for many purposes. This research documented the utilization of these naturalized alien plant species, particularly for traditional medicine. Data were obtained by interviewing 90 respondents in three locations around Cibodas Biosphere Reserve using questionnaire sheets. The questionnaire used the Index Cultural Significance framework to quantify the value of every species for traditional medicine. The results showed that the community used 41 naturalized alien plant species from 15 families. Asteraceae is the family with the most widely used species and has various medicinal benefits. The most frequently treated health problems are anti-inflammatory, dental and oral health, and fever. ICS value showed that the utilization rate is low, yet these plants have promising properties as sources of natural medicine. Moreover, the utilization of these alien plants can be an option in controlling these species to prevent the invasion of Gunung Gede Pangrango National Park. Keywords: alien plant species, Cibodas Biosphere Reserve, Index Cultural Significance, invasion risk, medicinal plant